Improving social adaptability among students at the University of the State Fire Service of the Ministry of Emergency Situations of Russia through the use of aerobic exercises - Tishchenko E.G. , (Theory and Practice of Physical Culture, 2025)
Objective of the study aims to determine the cumulative impact of a competitive team approach combined with aerobic exercise on improving the social adaptability of students with learning difficulties during physical training. Methods and structure of the study. Two groups of cadets from the Saint Petersburg University of the Ministry of Emergency Situations of Russia participated in the study.: There were 25 people in the control group (KG) and the same number in the experimental group (EG). In the control group, physical training classes were conducted according to a standard, approved curriculum. In the experimental group, the same program was used, but using the developed methodology. A new method of aerobic exercise in EG was introduced at the end of the main part of the lesson. It consisted of alternating a three-minute run with exercises from applied gymnastics: push-ups, body lifts from a prone position, a complex strength exercise and leg lifts lying on your back. In the process of pedagogical analysis, the parameters of social adaptation, physical fitness and functional status were evaluated. Results and conclusions. The inclusion of aerobic training using applied gymnastic elements in the program of high-speed movement and athletics classes helps to increase the range of functional capabilities of the trainees. Performing gymnastic exercises in an aerobic format has a positive effect on improving the functional state of the cardiovascular system. The introduction of aerobic training techniques into the educational process helps to develop a mechanism of social adaptation that ensures a balance of mental state in work and interaction among cadets with low academic performance.